Students’ Perceptions of Textbooks in Moroccan High Schools - Sakale, Sana (International Journal of Linguistics, Literature and Translation, 2020)
The objective of this study is to reveal the different perceptions, practices and problems related to speaking skills in Moroccan secondary education in general. The sample of the study consisted of students coming from different schools in the academy of Rabat-Salè-Zemmour-Zaer area. The results revealed a discrepancy between classroom activities, textbooks activities and the objectives of the guidelines set for the teaching of speaking in Moroccan high schools. The results also showed that the thematic importance, thematic variety and the preference of listening-focused textbooks including listening to songs are found to be what students perceive to be their most significant inclinations. The study concluded with a number of pedagogical implications for the teaching/learning process.